Christian Wolff’s system of Natural theology - Garay, Ignacio (Anales del Seminario de Historia de la Filosofía, 2024)
Christian Wolff’s arguments for the existence of God are mainly developed in his Theologia naturalis. Although this work presents a different argument in each of its two parts, Wolff calls it the “system of Natural theology”. This could be understood as suggesting that the arguments are not wholly independent one from another, but share a similar argumentative structure, even though Wolff does not say that explicitly. In this paper, my purpose is to argue that: 1) what these two arguments have in common is that they are both based on the notion of the being which has the reason of its existence in its essence. 2) This very notion is the metaphysical link between maximal perfection and necessary existence. 3) The difference between these two arguments is that they are developed in opposite directions. While the first one starts from necessary existence and concludes with maximal perfection, the second one starts from maximal perfection and concludes with necessary existence. In this paper, my purpose is to argue that: 1) what these two arguments have in common is that they are both based on the notion of the being which has the reason of its existence in its essence. 2) This very notion is the metaphysical link between maximal perfection and necessary existence. 3) The difference between these two arguments is that they are developed in opposite directions. While the first one starts from necessary existence and concludes with maximal perfection, the second one starts from maximal perfection and concludes with necessary existence.